Staphylococcus aureus Endocarditis as a Complication of Toxocariasis-Associated Endomyocarditis With Fibrosis: A Case Report. (7th September 2016) - Kuenzli, Esther; Labhardt, Niklaus; Balestra, Gianmarco; Weisser, Maja; Zellweger, Michael J.; Blum, Johannes
Abstract: Complications associated with Toxocara canis infection are rare. We present a case of a patient with Staphylococcus aureus endocarditis as a complication of an endomyocardial fibrosis caused by T canis . The epidemiological, pathological, and clinical features of this rare complication are described here.